The Effect of Philosophy for Children (P4C) Program on Working Memory and Frustration Tolerance in Sixth-Grade Students - Shahini Kevesk, Jamshid; Maredpour, Alireza; Mahmoudi, Armin (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to investigate the impact of the Philosophy for Children (P4C) program on working memory and frustration tolerance in sixth-grade elementary students.Methods and Materials: The study employed a quasi-experimental design with a pre-test, post-test, and one-month follow-up, including an experimental group (n = 25) and a control group (n = 25). Participants were selected using single-stage cluster random sampling from sixth-grade male students in Yasuj, Iran. The experimental group received 12 sessions of P4C intervention over six weeks, while the control group received no intervention. Data were collected using validated questionnaires for working memory and frustration tolerance. Statistical analyses included repeated measures ANOVA and Bonferroni post-hoc tests, conducted using SPSS 26.Findings: The results indicated a significant interaction effect between time and group for working memory (F(1.939, 93.095) = 97.203, p < 0.001, η² = 0.669) and frustration tolerance (F(1.457, 69.941) = 254.106, p < 0.001, η² = 0.841). Post-hoc comparisons revealed significant improvements in working memory scores in the experimental group from pre-test to post-test (p < 0.001) and pre-test to follow-up (p < 0.001). Frustration tolerance scores in the experimental group significantly decreased from pre-test to post-test (p < 0.001) and pre-test to follow-up (p < 0.001). No significant changes were observed in the control group.Conclusion: The findings demonstrate that the P4C program significantly enhances working memory and reduces frustration tolerance in elementary students. These results highlight the program's effectiveness in promoting cognitive and emotional development, underscoring its potential as a valuable educational intervention. Future research should explore long-term impacts and broader applications of P4C in diverse educational contexts.